Purposefulness of Improvement of Convict Re-socialization Implemented in the Remand Prison from the Perspective of the Personnel Engaged in the Process - Liukinevičienė, Laima; Mikalauskas, Donatas (Social Welfare: Interdisciplinary Approach, 2018)
Imprisonment establishments face a challenge to prepare an inmate for social integration. The presented research is based on assumptions provided by scientists who suppose that single quantitative indicators are not sufficient to measure effectiveness of re-socialisation of inmates being implemented in imprisonment institutions; subjective opinions of participants of the process are worth investigating, too. A qualitative research employing a semi-structured interview was conducted in Šiauliai Remand Prison in 2017; the results demonstrate the following: personnel working in social rehabilitation divisions notice changes, progress in the system of implementation of punishment, support the policy of modernisation of imprisonment establishments; however, they lack a systematic approach, compliance with the deadlines in implementation of the programmes, observe the problems of workload of the personnel and the lack of competences, environments required for implementation of individualised social rehabilitation of inmates.